2008
DOI: 10.1021/jp800984h
|View full text |Cite
|
Sign up to set email alerts
|

An in-Situ Chloride-Generated Route to Various One-Dimensional Nanostructures of Chromium-Based Compounds

Abstract: A convenient in-situ chloride-generated route has been developed to fabricate various novel one-dimensional nanostructures of Cr-based compounds including CrSi 2 , CrN and SiN x -coated CrSi 2 , CrN (with a trace of CrSi 2 ), and CrN-CrSi 2 intermediate composites for the first time. And the evolution of the products has been clearly illuminated on the basis of involved chemistry and the convincing characterization results. The diverse regulation of the products, the simplicity of the preparation procedure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Transition-metal silicides have attracted great scientific and technological interests due to their good conductivity, high melting point, excellent oxidation resistance as well as their potential applications in microelectronics, energy conversion and thermoelectric materials. [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, owing to the good compatibility with silicon substrates, some metal silicides show intriguing potential in various silicon-based optoelectronics and spintronics. 13,14 With the development of nanotechnology, it has been reported that the nanostructures of transition-metal silicides exhibit better performance in comparison with their bulk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transition-metal silicides have attracted great scientific and technological interests due to their good conductivity, high melting point, excellent oxidation resistance as well as their potential applications in microelectronics, energy conversion and thermoelectric materials. [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, owing to the good compatibility with silicon substrates, some metal silicides show intriguing potential in various silicon-based optoelectronics and spintronics. 13,14 With the development of nanotechnology, it has been reported that the nanostructures of transition-metal silicides exhibit better performance in comparison with their bulk.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 With the development of nanotechnology, it has been reported that the nanostructures of transition-metal silicides exhibit better performance in comparison with their bulk. 4 Great efforts have been devoted to the studies on the synthesis, properties and applications of low-dimensional silicides, and recently, many low-dimensional nanostructures of metal silicides, such as Fe 5 Si 3 /FeSi nanowires, 5,6 NiSi/Ni 2 Si nanowires, 7,8 CrSi 2 nanowires, 2,9,10 CoSi nanowires, 4 MnSi nanowires, 14 Pt 2 Si nanowires, 11 V 5 Si 3 nanotubes, 12 etc., have been prepared and in depth studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2c and d, it is seen that the gray product obtained on Si substrate at 750 • C is flocky nanorods with the hexagonal-cross-section and the uniform diameter of about 100-300 nm and the typical length of several micrometers, and the diffraction peaks are indexed to wurtzite AlN with lattice parameters a = 3.14 Å and c = 4.97 Å. The hexagonal-cross-section is a typical feature from hexagonal phase compounds [26].…”
Section: Resultsmentioning
confidence: 94%